Financial Inclusion, Productivity Shocks, and Consumption Volatility in Emerging Economies - Bhattacharya, Rudrani; Patnaik, Ila (World Bank, Washington, DC, 2015)
How does access to finance impact consumption volatility? Theory and evidence from advanced economies suggests that greater household access to finance smooths consumption. Evidence from emerging markets, where consumption is usually more volatile than income, indicates that financial reform further increases the volatility of consumption relative to output. This puzzle is addressed in the framework of an emerging economy model in which households face shocks to trend growth rate, and a fraction of them are financially constrained, with no access to financial services. Unconstrained households can respond to shocks to trend growth by raising current consumption more than the rise in current income. Financial reform increases the share of such households, leading to greater relative consumption volatility. Calibration of the model for pre- and post-financial reform in India provides support for the model’s key predictions.